STRATEGI PENGEMBANGAN PT XYZ DALAM AGRIBISNIS TEH HIJAU - Harris Darmawan; Arief Daryanto; Sukardi . (Jurnal Manajemen., 2015)
The growth of tea demand in Indonesia increased, while the national production was not sufficient. Therefore, import is increasing since Asean Free Trade Agreement (AFTA) enforced with 0% tariff import. The cheapness of imported tea causing domestic producers must increase their competitiveness, including XYZ Company as the biggest green tea producers in Indonesia. The objectives of this study are to: (1) to evaluate the internal and external environmental condition that affect value chain development of XYZ Co.; (2) to formulate alternative strategy for improve production efficiency and value chain effectiveness of XYZ Co.; (3) to determine priority strategy which can be implemented by XYZ Co., for value chain of tea development. The method of the study used was by using observation, in depth interviews and questionnaires to analyze company’s value chain, internal and external industry analysis, SWOT analysis, AHP-SWOT for priority strategic and implication managerial. The result of the study showed that the priority strategy were as follow: (1) enhancement capacity production of green tea; (2) build strategically partnerships; (3) production development; (4) product and marketing development; (5) enhancement operational standard; (6) enhancement publication of business